Applications of Synthetic Biotechnology on Carbon Neutrality Research: A Review on Electrically Driven Microbial and Enzyme Engineering - Zhuang, Xiaoyan; Zhang, Yonghui; Xiao, An-Feng; Zhang, Aihui; Fang, Baishan (Frontiers in Bioengineering and Biotechnology, 2022)
With the advancement of science, technology and productivity, the rapid development of industrial production, transportation and the exploitation of fossil fuels has gradually led to the accumulation of greenhouse gases and deterioration of global warming. Carbon neutral is a balance between absorption and emissions achieved by minimizing carbon dioxide (CO2) emissions from human social productive activity through a series of initiatives, including energy substitution and energy efficiency improvement. Then CO2 was offset through forest carbon sequestration and capture at last. Therefore, efficiently reducing CO2 emissions and enhancing CO2 capture is a matter of great urgency. Because many species own the natural CO2 capture properties, more and more scientists focused their attention on developing the biological carbon sequestration technique and further combined with synthetic biotechnology and electricity. In this paper, the advances of synthetic biotechnology method for the most promising organisms were reviewed, such as cyanobacteria, Escherichia coli and yeast, in which the metabolic pathways were reconstructed to enhance the efficiency of CO2 capture and product synthesis. Furthermore, the electrically-driven microbial and enzyme engineering process is also summarized, in which the critical role and principle of electricity in the process of CO2 capture is canvassed. This review provides detailed summaries and analysis of CO2 capture through synthetic biotechnology, which also pave the way for implementing electrically-driven combined strategies.